Long-Gap Esophageal Atresia: a Meta-Analysis of Jejunal Interposition, Colon Interposition, and Gastric Pull-Up - Gallo, Gabriele; Zwaveling, Sander; Groen, Henk; Van der Zee, David; Hulscher, Jan (European Journal of Pediatric Surgery, 2012)
Aim There is still no consensus about the optimal surgical approach for esophageal replacement in the case of long-gap esophageal atresia (LGEA) or extensive corrosive strictures. The aim of this article was to perform a meta-analysis comparing the most widely used techniques for esophageal replacement in children: jejunal interposition (JI), colon interposition (CI), and gastric pull-up (GPU).Methods Review of the English-language literature published in the past 5 years about esophageal replacement in children was done. The focus was on postoperative survival rate, morbidity (gastrointestinal complications such as anastomotic stenosis/leakage and respiratory complications such as pneumothorax, pneumonia, and atelectasis), and long-term follow-up when available. Among long-term gastrointestinal outcomes were dysphagia, reflux, and dumping; among long-term respiratory outcomes were recurrent pneumonia and recurrent aspiration leading to chronic lung disease. Data were computed by Comprehensive Meta-Analysis software (Version 2.2.064).Main Results A total of 15 studies (4 comparative retrospective, 8 retrospective, and 3 prospective) including 470 patients (264 LGEA) were identified; 344 (73%) patients underwent CI, 99 (21%) GPU, and 27 (6%) JI. Among these 15 studies, 9 provided data about long-term follow-up.Conclusion Proper prospective comparative studies are lacking. GPU and CI appear comparable regarding postoperative mortality, anastomotic complications, and graft loss. On the long-term, GPU seems to be associated with a higher respiratory morbidity but fewer gastrointestinal complications than CI. Based on this article only two series provide data about JI, and they show highly divergent results. JI appears to be a valid replacement technique when performed by experienced centers; however larger numbers are needed to assess the outcomes of this procedure.
Keywords: long-gap esophageal atresia; esophageal replacement; meta-analysis